Study on a method of slope stability analysis used for landfill slope - Bertram, Anak Thomas (Universiti Malaysia Sarawak, UNIMAS, 2006)
Land filling is a widely used method for the disposal of wastes. With increased levels of urbanization and the location of landfills in close proximity to highly populated areas, a proper constructed landfill can avoid bad odour and hazardous leachate which can be as a result of instability of slope in the landfill.